2004
DOI: 10.5380/ce.v9i2.1714
|View full text |Cite
|
Sign up to set email alerts
|

Prescrição De Enfermagem: Dos Motivos Da Não Realização Às Possíveis Estratégias De Implementação

Abstract: Quando se reflete sobre as desvantagens da prática de enfermagem não sistematizada, pode-se perceber o quanto se está deixando de valorizar a própria profissão, colaborando para sua estagnação. Esta situação pode ser visualizada, quando da não realização de prescrição de enfermagem, passando a equipe de enfermagem a guiar suas ações fundamentalmente pela prescrição médica, tornando aparentemente desnecessária a participação do enfermeiro nas tomadas de decisão. A implantação da Sistematização da Assistência de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
19

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 1 publication
0
5
0
19
Order By: Relevance
“…Percebeu-se que eles conheciam bem a primeira etapa do processo, porém, poucos se posicionaram nas fases de planejamento de enfermagem e implementação. O planejamento da assistência de enfermagem é um dos meios que o enfermeiro dispõe para aplicar seus conhecimentos técnico-científicos e humanos na assistência ao paciente e caracterizar sua prática profissional, colaborando na definição de seu papel (14) . Durante o plano de cuidados, o enfermeiro elabora as ações de enfermagem visando resolver os problemas encontrados durante a fase de diagnósticos.…”
Section: Discussionunclassified
“…Percebeu-se que eles conheciam bem a primeira etapa do processo, porém, poucos se posicionaram nas fases de planejamento de enfermagem e implementação. O planejamento da assistência de enfermagem é um dos meios que o enfermeiro dispõe para aplicar seus conhecimentos técnico-científicos e humanos na assistência ao paciente e caracterizar sua prática profissional, colaborando na definição de seu papel (14) . Durante o plano de cuidados, o enfermeiro elabora as ações de enfermagem visando resolver os problemas encontrados durante a fase de diagnósticos.…”
Section: Discussionunclassified
“…33 When a diagnosis is made, the nurse has an ethical and legal obligation to question what has occurred and provide a particular type of treatment or care. 36 According to the interviewees, many of the actions they use do not have a nursing diagnosis, but are developed through observations. At other times, a survey of diagnoses is prepared however there is no elaboration of a care plan: Failure to raise diagnoses interferes negatively with nursing prescription, which should individually organize the daily goals of each patient's care.…”
Section: Depending On the Nurse Or The Service We Do A Physical Exammentioning
confidence: 99%
“…24 The second study analyzes the use of material technologies in the ICU, such as monitors, mechanical ventilators, infusion pumps, defibrillators, pacemakers, computers and others, called by the authors as hard technologies; part of the idea that there is a strong relationship between the organization of nursing work in ICU and the use of technologies. 21 They concluded that the presence of obsolete materials, shortages and insufficient continuous training harm nursing work and cause suffering, dissatisfaction and an intensification in the work, among other consequences, with the use of technology not replacing the necessary personal interaction between caregivers and assisted subjects. 25 The third study describes the construction and implementation of a computerized nursing prescription in the ICU, in which the initiative and the process were considered positive and included the broad participation and compliance of the entire nursing staff.…”
Section: -26mentioning
confidence: 99%
“…The SNC and its institutionalization in appropriate records are a substantive component in attitude and practice that values the profession, however, it still does not receive due credit from nurses who often act only as facilitators of the work of other healthcare professionals and prioritize administrative and bureaucratic activities. 21 The shift change is a significant care management tool, organized and developed by the nursing staff. It is an important activity to ensure the adequate continuity of care, 24 hours a day, as well as team integration; besides being a rich space for communication and collective learning.…”
Section: Work Organization and Care Managementmentioning
confidence: 99%